ECOTOURISM IN SIMATUPANG VILLAGE: TURNING CHALLENGES INTO OPPORTUNITIES - Tambunan, Ellyta; Masatip, Anwari (PT. Hafasy Dwi Nawasena, 2024)
Simatupang Village is a village located in Muara Sub-district, North Tapanuli Regency.. Simatupang Village has great potential for the application of the ecotourism concept because of its abundant natural resources and strong culture, but it is not well managed. The purpose of this research is to find out the concept of ecotourism in Simatupang Village and to find out the development of sustainable tourism in Simatupang Village. The research method used is a qualitative research method with a descriptive approach. The data collection techniques used were observation, interviews, and literature study, and the data analysis technique used was descriptive qualitative analysis. The concept of ecotourism in Simatupang Village is an ecotourism concept based on nature conservation and utilizing the environment and culture inherent in the community as a tourist destination that can increase income and prosper the community.